Pola Pemahaman Keagamaan HMI DIPO, HMI MPO, KAMMI UIN Suska Riau terhadap Kesadaran Pluralitas - Khotimah Khotimah (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
In a social context, religious understanding usually can not stand alone. Social factors, environment, education, and politics go hand in influencing one's religious understanding. Thus, moderate or radical understanding of a person is not merely influenced by the doctrine of religion, but also by various factors which in turn gave birth attitudes and social behavior. View and attitude of the organization groups on a plurality of consciousness, can not be separated from how the interaction of the people (in group ) is done, both individually and with community groups welcome (out group). Social changes often occur which are a response from the various interactions, which then led to a reaction or attitude. This reaction, could form the opposition, cooperation, and differentiation